Experimental Investigation on Cyclopentane-Methane Hydrate Formation Kinetics in Brine - Zang, Xueru; Lv, Qiunan; Li, Xiaosen; Li, Gang (Energy & Fuels, 2017)
On the basis of the hot brine in situ seafloor prepared for marine NGHs exploitation, formation kinetic behavior of cyclopentane (CP)-methane hydrate was studied at various depths of ocean water. The effects of the temperature, pressure, gas liquid ratio, and ratio of CP/liquid phase on gas uptake were investigated to reveal the affecting factors of the hydrate rapid formation. The experimental results indicated that the driving force played an important role in the hydrate formation. In addition, the CP/liquid phase ratio of 5% was beneficial to gas uptake. When the conditions of driving force and the CP/liquid phase ratio were very favorable for hydrate formation, the gas uptakes slightly change with the gas liquid ratio. In contrast, a smaller gas liquid ratio was conducive to gas uptake.